PARTISIPASI MASYARAKAT DALAM JUDICIAL REVIEW DI MAHKAMAH KONSTITUSI SEBAGAI WUJUD MENGUATKAN PRINSIP NEGARA HUKUM KESEJAHTERAAN - Firmansyah R, Adithya Tri (Esensi Hukum, 2023)
Society participation is an important discourse to study, especially in the paradigm of a democratic rule of law which principally requires society involvement in its implementation. Of course this implementation also includes the formation of laws, where the community has a crucial position to be involved in ensuring that laws achieve their ideal goal of prosperity. However, in the current dynamics of enactment of laws it seems to be a manipulative process, for purposes that are contrary to good intentions. When such conditions occur, society can use constitutional means to evaluate laws that have the potential to violate their rights through judicial review. Therefore this research wants to examine society participation in judicial review at the Constitutional Court as a form of strengthening the principle of a welfare state. This study uses a normative juridical method with a statute approach. The results of this study concluded that the state is responsible for ensuring the welfare of every citizen. To achieve this welfare requires a law to regulate it. However, if the law produced by the state government is far from aiming to prosper, then the society can take a role by filing a request for judicial review at the Constitutional Court. The activity of filing a request for judicial review is an effort for the society to actively participate in evaluating laws to strengthen the principle of a welfare state which has the basic idea that every legal product must have an aspirational element for the society.